Comparative molecular and cytogenetic methods can clarify meiotic incongruities in Avena allopolyploid hybrids - Nikoloudakis, Nikolaos; Katsiotis, Andreas (My University, 2015)
Avena longiglumis is a diploid species that has been proposed as the A-genome donor of allopolyploid oats. In order to clarify its participation in the evolution of oats, a triploid A. magna × A. longiglumis hybrid was synthesized and studied, via a concurrent combination of cytogenetic and molecular techniques. The analysis of pollen mother cells revealed that synapsis percentage and chromosome chiasmata per cell were low; still they were the highest recorded among the diploid species used as pollinators of AC-genome tetraploids. In addition, genomic in situ hybridization revealed extensive chromosomal translocations among the allopolyploids that may have contributed to the low chromosomal affinity. Furthermore, amplified fragment length polymorphisms revealed the extensive genomic modifications that followed the interspecific hybridization, depicted mainly as the loss of parental bands (51.29%) and the creation of novel bands in the progeny (15.73%). As a result, the combination of cytogenetic and molecular techniques can elucidate meiotic incongruities that can make the unraveling of oat evolution challenging.
Keywords: AFLPs; FISH; GISH; Interspecific hybridization; Oat